Treatment of Kind of Planting Media and Different Spacing for Growth of Pakcoy Mustard Plants (Brassica rapa L) by Method Hidroponik Wick System. - M Abror; Jefrisal Mirza Arrohman (Nabatia, 2019)
The purpose of this study was to determine the effect of planting media and different spacing on the growth of Pakchoi mustard plants using the wick hydroponic system. This research is conducted at the Green House of the Faculty of Science and Tech- nologyMuhammadiyah Sidoarjo University from January to March 2019.using factorial Randomized Block Design (RBD) repeatet 3 times with the first factor planting media consisting of, dacron (M1), planting media bagasse (M2), rockwol (M3) planting media. The second factor is the plant space which is consisting of, 10x10 cm (JT1), 15x15 cm (JT2), 20x20 cm (JT3). Data analysis showed that on the observation of leaf area and wet weight per plot there are a real interaction with the planting medium with spacing. The treatment of planting media significantly affected leaf area, wet weight per plant, wet weight per plot, number of leaves and root volume in the rockwol M3 planting media treatment give better results. In the treatment of spacing gives a significant effect on leaf area, weight per plot, and number of leaves, in treatment of 10x10 cm JT3 spacing gives better results.